2018
DOI: 10.1212/wnl.0000000000005412
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Antibiotics in Stroke Study (PASS)

Abstract: Preventive ceftriaxone has a probability of 0.7 of being less costly than standard treatment per unit decrease in mRS and per QALY gained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 13 publications
0
7
1
14
Order By: Relevance
“…One of the largest studies, which included 19,063 first-time stroke patients, indicated that the risk of stroke was highest during the first 3 days after the diagnosis of respiratory tract infection (IR = 3.19 95%CI 2.81-3.62) or urinary tract infection (IR = 2.72 95%CI 2.32-3.20). However, in the following PASS (preventive antibiotics in stroke study), preventive ceftriaxone did not improve functional outcomes in patients with acute stroke [37]. In our study, the most significant infections were Helicobacter pylori(HP), virus and certain atypical microorganisms, including amoebiasis, legionellosis and vibrio cholerase, which were not covered by ceftriaxone.…”
Section: Discussioncontrasting
confidence: 57%
“…One of the largest studies, which included 19,063 first-time stroke patients, indicated that the risk of stroke was highest during the first 3 days after the diagnosis of respiratory tract infection (IR = 3.19 95%CI 2.81-3.62) or urinary tract infection (IR = 2.72 95%CI 2.32-3.20). However, in the following PASS (preventive antibiotics in stroke study), preventive ceftriaxone did not improve functional outcomes in patients with acute stroke [37]. In our study, the most significant infections were Helicobacter pylori(HP), virus and certain atypical microorganisms, including amoebiasis, legionellosis and vibrio cholerase, which were not covered by ceftriaxone.…”
Section: Discussioncontrasting
confidence: 57%
“…A recent cost-effectiveness study of PASS showed that three months after stroke, the number of quality-adjusted life years (QALYs) was significantly higher in the ceftriaxone-treated patients, compared with the control group ( p = 0.006) and that preventive ceftriaxone in adults with acute stroke is indeed cost-effective. 43 Whether costs justify the increasing use of antibiotics, however, remains subject of debate.…”
Section: Future Directions: “Can We Conclude That No Further Researchmentioning
confidence: 99%
“…Amelia Boehme, PhD, contributes a blog titled "Prophylactic antibiotic use in stroke patients," in reference to the article by Westerndorp et al, 1 "Preventive Antibiotics in Stroke Study (PASS): A cost-effectiveness study," about ceftriaxone vs standard stroke unit care without preventive antibiotics therapy. In the primary publication of PASS, prophylactic ceftriaxone did not improve the modified Rankin Scale score at 3 months.…”
Section: Editors' Blogmentioning
confidence: 99%